Analysis of Ta’widh Law in Murabahah Financing from the Perspective of Islamic Law and Positive Law - Marjani Putri, Muslifah; Nashirudin, Muh. (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
Analysis of the law of ta’widh in murabahah financing is an in-depth study of the application of the concept of ta’widh in sharia financial transactions, especially in the type of murabahah financing. This study involves two main perspectives, namely the perspective of Islamic law and positive law. The case study at KSPPS BMT At-Tunnisa Jumapolo Branch is used as a context to obtain a more concrete and applicable understanding regarding the implementation of ta’widh in sharia financial practices. From the perspective of Islamic law, ta’widh is seen as an important mechanism for ensuring fairness in financial transactions. The principle of justice (Al-'Adl) and the prohibition of usury are the main foundations for implementing ta’widh. The application of ta’widh in concrete cases at KSPPS BMT At-Tunnisa Jumapolo Branch will be evaluated from a sharia perspective to assess whether the policies and practices of ta’widh are in accordance with the principles of Islamic law. Meanwhile, from a positive legal perspective, ta’widh is seen as part of the compensation mechanism in contracts regulated by statutory regulations. The analysis will involve a study of regulations in the financial sector, such as OJK regulations, which regulate fines in sharia financing. The implementation of ta’widh in BMT cases will also be evaluated from a positive legal perspective to ensure compliance with applicable regulations. BMT's internal policies regarding ta’widh, loss calculation procedures, cases involving ta’widh, and conformity with sharia principles and positive law are the objects of in-depth analysis. The method used in this research is qualitative with a case study method. It is hoped that the results of this analysis will provide a comprehensive understanding of the application of ta’widh in sharia financial practices, as well as recommendations for improving policies and practices in accordance with the principles of Islamic law and positive law.